Intercellular Resistance to BRAF Inhibition Can Be Mediated by Extracellular Vesicle–Associated PDGFRβ - Laura J. Vella (Neoplasia: An International Journal for Oncology Research, 2017)
Treatment of BRAF mutant melanoma with kinase inhibitors has been associated with rapid tumor regression; however, this clinical benefit is short-lived, and most patients relapse. A number of studies suggest that the extracellular environment promotes BRAF inhibitor resistance and tumor progression. Extracellular vesicles, such as exosomes, are functional mediators in the extracellular environment. They are small vesicles known to carry a concentrated group of functional cargo and serve as intercellular communicators not only locally but also systemically. Increasingly, it is reported that extracellular vesicles facilitate the development of drug resistance in cancer; however, their role in BRAF inhibitor resistance in melanoma is unclear. Here we investigated if extracellular vesicles from BRAF inhibitor–resistant melanoma could influence drug sensitivity in recipient melanoma cells. We demonstrate that the resistance driver, PDGFRβ, can be transferred to recipient melanoma cells via extracellular vesicles, resulting in a dose-dependent activation of PI3K/AKT signaling and escape from MAPK pathway BRAF inhibition. These data suggest that the BRAF inhibitor–sensitive phenotype of metastatic melanoma can be altered by delivery of PDGFRβ by extracellular vesicles derived from neighboring drug-resistant melanoma cells.